Methyl (E)-3,5-dimethoxy-2-{[2-(4-methoxybenzoyl)hydrazin-1-ylidene]methyl}benzoate - Naz, Humera (International Union of Crystallography, 2012)
In the title compound, C(19)H(20)N(2)O(6), the azomethine [C=N = 1.269 (2) Å] double bond adopts an E conformation and the dihedral angle between the planes of the benzene rings is 17.41 (11)°. In the crystal, inversion dimers linked by pairs of N—H⋯O hydrogen bonds generate R (2) (2)(16) loops. The dimers are connected by C—H⋯O and C—H⋯N hydrogen bonds, forming sheets lying parallel to (100).